2012
DOI: 10.1590/s0100-736x2012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Leukograms of healthy Holstein calves within the first month of life

Abstract: To establish reference values and to assess the influence of age on the leukograms of healthy Holstein calves, blood samples were obtained from 300 animals. These samples were distributed equally (n=20) among 15 experimental groups according to age: birth to 8 hours, 9 to 16 hours, 17 to 24 hours, 2 days, 3 days, 4 days, 5 days, 6 to 7 days, 8 to 9 days, 10 to 11 days, 12 to 13 days, 14 to 15 days, 16 to 20 days, 21 to 25 days and 26 to 30 days of age. The maximum numbers of leukocytes (9,305.0/mL), segmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
2
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 7 publications
7
16
2
15
Order By: Relevance
“…The growth indices of the calves from the 33 days of experiment are presented in number can be observed, similarly to the other study (Benesi et al, 2012).…”
Section: Resultssupporting
confidence: 67%
“…The growth indices of the calves from the 33 days of experiment are presented in number can be observed, similarly to the other study (Benesi et al, 2012).…”
Section: Resultssupporting
confidence: 67%
“…Most studies involving polymorphonuclear leukocytes in calves used leucogram despite the different techniques employed, these studies also found higher numbers of neutrophils in the first days of life (Benesi et al, 2012;Menge et al, 1998). Changes in the population of CH138 + cells in the first days of life may be associated with the stress at delivery and birth, especially because some animals in this study were pulled at birth, increasing the blood concentration of endogenous steroids and migration of these cells from the marginal pool to circulation (Benesi et al, 2012). Therefore, the major proportion of circulating neutrophils recorded before the colostrum intake and in the first days of life of the calves may be a mechanism of immune hand, since many functions related to these cells are immature or incomplete (Menge et al, 1998).…”
Section: Ajavsmentioning
confidence: 99%
“…At this time, despite a transient increase in number of polymorphonuclear leukocytes (PMN), there is a decrease of their functional activity, considering the rates of phagocytosis and bactericidal capacity (Benesi et al, 2012;Chase et al, 2008;Morein et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Notou-se aumento na contagem deste tipo celular a partir do nascimento, com os valores máximos aos 30 dias de idade em ambos os grupos (Quadro 2), corroborando com os achados de Mohri et al (2007) e Benesi et at. (2012a) Não se constatou diferença na contagem de neutrófilos segmentados entre os grupos no decorrer do período experimental (Quadro 2).…”
Section: Resultsunclassified
“…(2012a) Não se constatou diferença na contagem de neutrófilos segmentados entre os grupos no decorrer do período experimental (Quadro 2). A redução gradativa na contagem desse tipo celular até os 30 dias de vida corrobora os achados de Fagliari et al (1998), Mohri et al (2007) e Benesi et al (2012a).…”
Section: Resultsunclassified